Ayat-Ayat Al-Qur’an dalam Bingkai Media: Studi Atas penafsiran ayat-ayat al-Qur’an dalam Koran Harian Bangsa - Adrika Fithrotul Aini (LPPM IAIN Sultan Amai Gorontalo, 2015)
This article will discuss the interpretation of the Qur’anic verses in Harian Bangsa newspaper, specifically appeared in rubric of “Tafsir al-Qur’an Aktual.” The article includes themes in Desember 2014 and Januari 2015 only. From the explanation of Qur’anic exegesis appeared in the media, this article will discuss about the values contained to inform the religious teaching with comparing between Qur’an’s exegesis the earliest issues. The analysis shows that indeed the content of Tafsir al-Qur’an Aktual rubric is more oriented on the social religious.